Perancangan Keamanan Jaringan Untuk Mencegah Terjadinya Serangan Bruteforce Pada Router - Bahri, Syaiful (PT. INOVASI TEKNOLOGI KOMPUTER, 2023)
The development of information technology demands the need for effective network security design to protect communications infrastructure, especially routers, from brute force attacks. Brute force attacks are a method commonly used by attackers to try password combinations repeatedly until they successfully enter the system. This research aims to design a network security solution that can prevent routers from being exposed to brute force attacks. This research combines technical and conceptual approaches to identify potential vulnerabilities in routers and develop security strategies that can overcome these challenges. Security methods include implementing strong password policies, real-time attack detection, and improving response to suspicious access attempts. By implementing this security solution, it is hoped that it can increase the level of network security, reduce the risk of brute force attacks, and protect data and services that pass through routers. The results of research using Mikrotik RouterOs show that RouterOs is able to defend against bruteforce attacks. The attack that was attempted was successfully blocked by RouterOs